2006
DOI: 10.1007/s11547-006-0038-z
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the phosphocreatine T1 time constant using a clinical NMR scanner

Abstract: On the phantom, the average T1 values for the various protocols and mathematical models used proved to differ widely, ranging from 0.61 s to 7.20 s. On volunteers, the T1 values obtained at rest and during exercise were not significantly different--0.91 s on average. Correction of this T1 value with the results obtained using the phantom provides a T1 value of 5.73 s, which is comparable with the value reported in the literature for resting conditions only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Creatine phosphate sodium, used for the synthesis of adenosine triphosphate (ATP), can reserve energy for cardiac muscles, skeletal muscles and the brain; and the hydrolysis of ATP provides energy for actomyosin contraction. 8 , 16 , 17 Studies have reported that an intravenous injection of creatine phosphate sodium (0.5–1.0 g) can rapidly supply energy to compensate for ATP deficiency caused by surgical trauma and hypoxia, improve the energy metabolism of cells under ischaemic hypoxia, increase glucose utilization, enhance myocardial contractility and improve tissue (especially myocardial) tolerance to hypoxia. 18 , 19 Due to the fact that the elderly’s ability to reserve myocardial energy is poorer than that of the young, 19 an intravenous infusion of 1.0 g creatine phosphate sodium was used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Creatine phosphate sodium, used for the synthesis of adenosine triphosphate (ATP), can reserve energy for cardiac muscles, skeletal muscles and the brain; and the hydrolysis of ATP provides energy for actomyosin contraction. 8 , 16 , 17 Studies have reported that an intravenous injection of creatine phosphate sodium (0.5–1.0 g) can rapidly supply energy to compensate for ATP deficiency caused by surgical trauma and hypoxia, improve the energy metabolism of cells under ischaemic hypoxia, increase glucose utilization, enhance myocardial contractility and improve tissue (especially myocardial) tolerance to hypoxia. 18 , 19 Due to the fact that the elderly’s ability to reserve myocardial energy is poorer than that of the young, 19 an intravenous infusion of 1.0 g creatine phosphate sodium was used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Positions and areas (signal intensities) of spectral peaks were calculated by means of the time-domain VARPRO/minpack fitting program, using the appropriate starting values and without any prior knowledge. To ensure that each spectrum of a given data set had the same saturation level, the first three spectra of each dataset were discarded and no other correction for partial saturation was made, since the T 1 relaxation time of PCr remains constant between rest and steady-state exercise (Cettolo et al 2006).…”
Section: Analysis Of Spectramentioning
confidence: 99%
“…All the phosphagens signal intensities (Pi, PCr, cATP, aATP and bATP) were obtained by fitting the corresponding peaks in the time-domain with classical constraints used for a 1.5 T spectrometer (van den Boogart 1997). The so obtained signal intensities were then brought back to the completely relaxed condition applying the appropriate saturation factors calculated on the basis of the apparent spin-lattice relaxation time (T 1 ) (Gadian 1982) of the different phosphagens obtained applying the same acquisition parameters as those of the present experimentation (Cettolo et al 2006). Finally, resting [PCr] was estimated by comparing the area under the PCr peak with that of the bATP, assuming an average ATP concentration of 5.72 mmol kg -1 wet weight for the resting muscle (Bangsbo et al 1993).…”
Section: Assessment Of Absolute Resting Pcr Concentrationmentioning
confidence: 99%
See 2 more Smart Citations